2009
DOI: 10.1074/jbc.m109.053876
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular 2′,3′-cAMP Is a Source of Adenosine

Abstract: We discovered that renal injury releases 2,3-cAMP (positional isomer of 3,5-cAMP) into the interstitium. This finding motivated a novel hypothesis: renal injury leads to activation of an extracellular 2,3-cAMP-adenosine pathway (i.e. metabolism of extracellular 2,3-cAMP to 3-AMP and 2-AMP, which are metabolized to adenosine, a retaliatory metabolite). In isolated rat kidneys, arterial infusions of 2,3-cAMP (30 mol/ liter) increased the mean venous secretion of 3-AMP (3,400-fold), 2-AMP (26,000-fold), adenosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 41 publications
5
91
0
Order By: Relevance
“…This is consistent with the fact that we previously reported on axonal injury, rather than neuronal death, and argues against a major role for ischemia in the initial 24 h. Although 5¢-AMP (produced from ATP/ADP metabolism) is considered the major precursor for adenosine, recent studies suggest that adenosine may also derive from the metabolism of 2¢,3¢-cAMP to 3¢-AMP or 2-AMP, with subsequent metabolism to adenosine. 25 Our current study reveals that brain tissue levels of adenosine are strongly associated with 2¢-AMP, but not 5¢-AMP, consistent with 2¢-AMP as a source of adenosine in the injured brain. It has been shown that 934 KOCHANEK ET AL.…”
Section: Atp Purines and Adenosinesupporting
confidence: 50%
See 1 more Smart Citation
“…This is consistent with the fact that we previously reported on axonal injury, rather than neuronal death, and argues against a major role for ischemia in the initial 24 h. Although 5¢-AMP (produced from ATP/ADP metabolism) is considered the major precursor for adenosine, recent studies suggest that adenosine may also derive from the metabolism of 2¢,3¢-cAMP to 3¢-AMP or 2-AMP, with subsequent metabolism to adenosine. 25 Our current study reveals that brain tissue levels of adenosine are strongly associated with 2¢-AMP, but not 5¢-AMP, consistent with 2¢-AMP as a source of adenosine in the injured brain. It has been shown that 934 KOCHANEK ET AL.…”
Section: Atp Purines and Adenosinesupporting
confidence: 50%
“…Brain samples placed in 1-propanol were analyzed for 3¢,5¢-cAMP (cyclic adenosine monophosphate), 2¢,3¢-cAMP, 5¢-AMP, 3¢-AMP, 2¢-AMP, adenosine, and inosine using our standard liquid chromatography/tandem mass spectrometry (LC-MS/MS) purine assay with selected reaction monitoring (SRM). 25 Brain samples placed in perchloric acid were analyzed for ATP and adenosine diphosphate (ADP), also using LC-MS/MS, but with modifications of our standard purine assay. For ATP and ADP, the high-performance liquid chromatography reversed-phase column was a Bonus-RP (1 · 50 mm; 3.5 lm; Agilent Technology, Lexington, MA), and the mobile phase consisted of two eluents.…”
Section: Measurement Of Purinesmentioning
confidence: 99%
“…Renal vascular resistance (RVR) and mesenteric vascular resistance (MVR) were calculated by dividing the MABP by the RBF or MBF, respectively. In nine control rats and 12 guanosine-treated rats, urine collected before the infusions of adenosine was analyzed for guanosine, adenosine, and inosine using high-performance liquid chromatography-tandem mass spectrometry as previously described (Jackson et al, 2009). It was not possible to compare the urine levels of these purines in the presence of adenosine because urine volumes were severely reduced in those rats receiving guanosine plus adenosine.…”
Section: Methodsmentioning
confidence: 99%
“…Adenosine, AMP, and inosine concentrations in the samples were determined using a triple quadrupole mass spectrometer (TSQ QuantumUltra, ThermoFisher Scientific, San Jose, CA) as previously described (26).…”
Section: Methodsmentioning
confidence: 99%